Advanced LI-FI Technology for Voice and Data Transmission with Device Control - D. Loganathan, A. Kingsly Jabakumar, K. Shruthi, R. Sathish kumar, M. Swathy (Mathematical Statistician and Engineering Applications, 2023)
Now a days, Data transmission without using any network is very tedious job to do. In this paper, data and audio is transmitted and received through visible lights and control the devices. The data is generated by microcontroller (tx) then transmitted through LED, these data can be received by photo detector and displayed on microcontroller. It is an advanced technology and the accuracy is more. In this paper data communication, controlling the devices and as well as transmission of audio through visible light is achieved. Now a day, Wi-Fi is commonly used technology but the radiations are hazardous for human health so Li-Fi is the one which eliminated the wireless technology like Wi-Fi and transmits the data by using light.